2018
DOI: 10.1097/iae.0000000000001698
|View full text |Cite
|
Sign up to set email alerts
|

Wrinkled Vascularized Retinal Pigment Epithelium Detachment Prognosis After Intravitreal Anti-Vascular Endothelial Growth Factor Therapy

Abstract: The evolution of v-PED after intravitreal anti-vascular endothelial growth factor injection is still difficult to predict despite intense clinical research in this topic. In our study, we noticed that w-PED might be a phenotypic prognosis factor for better visual acuity and longer maximal recurrence-free interval.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 50 publications
1
4
0
Order By: Relevance
“…Particularly, they found the growth in PEDs' greatest linear diameter to be associated with the maintenance of a quiescent phenotype, whereas the growth in PEDs' maximal height was associated more frequently with the development of an exudative phenotype. The latter was confirmed by studies by Lam et al [44] and Serra et al [43]. These suggest that PEDs' "contour" morphology might be indicative of a possible future exudative development.…”
Section: Discussionsupporting
confidence: 56%
“…Particularly, they found the growth in PEDs' greatest linear diameter to be associated with the maintenance of a quiescent phenotype, whereas the growth in PEDs' maximal height was associated more frequently with the development of an exudative phenotype. The latter was confirmed by studies by Lam et al [44] and Serra et al [43]. These suggest that PEDs' "contour" morphology might be indicative of a possible future exudative development.…”
Section: Discussionsupporting
confidence: 56%
“…In addition, in our study, brolucizumab was also efficacious in reducing PED height that significantly decreased during follow-up ( p = 0.020), thus confirming the possible role of PED as a biomarker. Different authors found a connection between the growing PED horizontal diameter and the maintenance of a quiescent CNV type, whereas the increase in vertical diameter being related to an exudative state, reinforcing possible use of PED as a biomarker [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…13,[31][32][33] Reduction in fibrovascular PED height in this context may be the result of fibrocytes and other inflammatory cells that contract, as evidenced by the presence of overlying RPE wrinkling. 34 Vascularized serous PEDs that acutely collapse because of VEGF-mediated reduction of fluid and leakage may transition to a chronic multilayered fibrovascular PED after chronic therapy.…”
Section: Discussionmentioning
confidence: 99%